The Role of Teachers in Realizing the Goals of Islamic Education - Trisnawaty Trisnawaty; Herawati Herawati; Tatang Hidayat (Islamic Research, 2022)
This research was motivated by the condition of the secular education system which creates an education system that is far from the goals of Islamic education, marked by the non-optimal role of the teacher. The purpose of this study is to determine the role of teachers in realizing the goals of Islamic education. This present study employed a qualitative approach in the form of a literature study. Based on the results of the discussion, the purpose of education in Islam is to foster human character, by forming an Islamic personality (Syakhsiyyah Islamiyyah), mastering Islamic philosophy, and mastering the sciences of life (science, technology, and expertise). Therefore, in the learning process, teachers have an important role in realizing educational goals. The role of the teacher is not only the transfer of knowledge but the teacher should be able to be a role model for personality. It resulted from the teaching method chosen by the teacher. Teachers must apply directly teaching methods, such as exemplary good behavior and character, teaching the Shari'a gradually, not excessively, paying attention to the different conditions of each learner, the method of conversation and logical considerations, the method of analogy and similitude, imagery method, a method by combining words and hand signals, targhib and tarhib methods (motivation and threats).